2019
DOI: 10.1002/ijgo.12906
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of labor progression by intrapartum ultrasonography among term nulliparous women

Abstract: Objective To assess cervical dilation, fetal head station, and fetal head position by intrapartum ultrasonography and to compare the approach with digital vaginal examination (DVE). Methods An observational study conducted from October 2015 to January 2017 among term nulliparous women in active labor at a tertiary hospital in Delhi, India. Cervical dilation, head station, and head position were assessed by DVE, followed by ultrasonography within 10 minutes. The women's preference was also evaluated. Results Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This comes in comparison with the study of Mohan et al, 7 In the current work, we revealed that the embryonic head position distribution in the study group females according to ultrasonography and DVE examination and the agreement between them. The embryonic head position couldn't be identified in 21 (24.7%) of the females by the DVE examination.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This comes in comparison with the study of Mohan et al, 7 In the current work, we revealed that the embryonic head position distribution in the study group females according to ultrasonography and DVE examination and the agreement between them. The embryonic head position couldn't be identified in 21 (24.7%) of the females by the DVE examination.…”
Section: Discussionsupporting
confidence: 82%
“…It is suggested that females must be permitted to labour for extended periods so that vaginal birth can be done. 7 Conventionally, the evaluation and management of a female in labour is built on clinical results. The labour arrest diagnosis and decisions concerning the timing or type of intervention rely mostly on digital evaluation of cervical dilatation and embryonic head station and location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study where the progress of labour was assessed both traditionally (per vaginam) and by means of intrapartum sonography, a survey of patients' opinions and experiences revealed that 87% of them would prefer to be examined solely by transperineal ultrasound during their next birth (35) . Obstetricians have an equally favourable opinion of the method.…”
Section: Intrapartum Ultrasound and The Comfort Of Women In Labourmentioning
confidence: 99%
“…In the majority of studies, a single assessment of sonographic parameters was performed in either the first or second labor phase 30,[32][33][34][35] . Moreover, few studies have developed predictive models associated with successful internal rotation and vaginal delivery.…”
Section: Introductionmentioning
confidence: 99%